Trends of Mobile Marketing Studies in the Two Last Decades: A Scoping Review using Bibliometric Analysis - Manao, Alwinda; Hurriyati, Ratih; Hendrayati, Henny; Sudarman , Sudarman; Akbar, Muhammad Yaumal; Amelia, Riska; Rafliansyah, Farizki Maulana (Journal of Posthumanism, 2025)
Mobile marketing is one of the novel ways to increase the economic growth in the digital era by creating the successful industries and businesses. At least in the last two decades, numerous studies published in journals and conference proceedings have examined various aspects of mobile marketing, including consumer behavior, technological integrations, and campaign effectiveness. These studies, however, often focus on specific case studies or isolated advancements rather than providing a comprehensive overview by identifying overarching trends and highlight potential areas for future mobile marketing researches. A scoping review was applied to highlight the trends and innovations in mobile marketing studies over the last two decades. Some bibliometric analyses, including performance, citation, co-authorship, and co-occurrence were conducted on 359 documents within article, review, and conference paper collected from the Scopus database. Results underscored the pivotal role of technology in shaping mobile marketing, with advancements, such as smartphones, augmented reality, and artificial intelligence driving innovation. Countries, such as the United States, the United Kingdom, China, Germany, and South Korea have emerged as dominant contributors to mobile marketing research, reflecting their strong technological and economic ecosystems. The review also revealed that activities, such as m-commerce, m-payment, and electronic marketplaces have become central to the evolution of mobile marketing practices. Predictors, such as behavioral intention, technological innovation, and profitability were identified as significant factors influencing mobile marketing adoption and success. This review provides a valuable foundation for understanding the trajectory of mobile marketing research and its implications for academia, industry, and policy.